A review study of cognitive design research on colors from a visual psychological perspective - Singh, Monica; Singari, Ranganath Muttanna; Bholey, Mihir (International Journal of Experimental Research and Review, 2023)
This review study aims to explore the relationship between color psychology and cognitive design in various environments, with a focus on human perception and visual comfort. By analysing existing literature, we identify gaps and weaknesses in the research and suggest ways to improve the design of spaces such as hospitals, public libraries, and colleges using color application. The study reveals that the use of colors can significantly affect users' emotions, stress levels, and visual discomfort, and can create aesthetically pleasing environments. We also suggest that more research is needed to better understand the impact of colorful and interesting environments on human psychology and well-being. Overall, this study highlights the importance of considering human psychology in color application design and offers insights into how to enhance the nature of existing spaces through the use of color.